The significance of free light-chain ratio in light-chain monoclonal gammopathy of undetermined significance: a flow cytometry sub-study of the iStopMM screening study - Jón Þórir Óskarsson; Sæmundur Rögnvaldsson; Sigrun Thorsteinsdottir; Thorir Einarsson Long; Andri Ólafsson; Elias Eythorsson; Ásbjörn Jónsson; Brynjar Viðarsson; Páll T. Önundarson; Bjarni A. Agnarsson; Róbert Pálmason; Margrét Sigurðardóttir; et al. (Blood Cancer Journal)
Abstract Light-chain (LC) monoclonal gammopathy of undetermined significance (MGUS) is a precursor of multiple myeloma (MM) and related conditions. LC-MGUS is characterized by free light-chain (FLC) levels outside defined reference intervals, indirectly indicating underlying plasma cell (PC) monoclonality. Next-generation flow cytometry (NGF) was used to evaluate clonal PC presence in bone marrow (BM) samples from individuals with LC-MGUS in the iStopMM study, aiming to assess the predictive value of the FLC ratio for clonal PC presence and its prognostic implications. BM samples from 61 individuals with LC monoclonal gammopathy were analyzed. Clonal plasma cells were detected in 53.6% of LC-MGUS samples (n = 28) and in all samples from individuals with more advanced conditions (n = 33). The FLC ratio was predictive of clonal PC presence for kappa-involved FLC ratios (p < 0.05; n = 42), with an optimal cutoff of 3.15 (96.7% sensitivity, 91.7% specificity). Of 195 individuals with kappa-involved LC-MGUS in follow-up within the iStopMM study, none with FLC ratios >1.65 to 3.15 progressed to MM (n = 124), whereas 4/71 (5.6%) with FLC ratios >3.15 progressed over median follow-up of 55 months. These findings support using a kappa-involved FLC ratio cutoff of >3.15 to more accurately identify individuals at increased risk of developing symptomatic PC disorders.